Fungi from palms in Argentina. 1 - Capdet, Mariana (2010)
Thirteen ascomycetes are reported from Argentina from fallen woody parts of three palms in two national parks. Berkleasmium corticola, B. sinense, Brachysporiella gayana, Dictyosporium cocophylum, D. zeylanicum, Endocalyx melanoxanthus var. melanoxanthus, Ernakulamia cochinensis, Musicillium theobromae, Sporidesmium macrurum, and Stachylidium bicolor are new records for Argentina. Melanochaeta hemipsila is reported for the first time as a teleomorph in this country.